Giant Brunner's Gland Hamartoma of the Duodenal Bulb Presenting with Upper Gastrointestinal Bleeding and Obstruction - Ju Hyoung Lee; Kyeong Min Jo; Tae Oh Kim; Jong Ha Park; Seung Hyun Park; Jae Won Jung; So Chong Hur; Sung Yeun Yang (Korean Society of Gastrointestinal Endoscopy, 2016)
Brunner's gland hamartomas are small benign lesions that are most commonly found in the bulb of the duodenum. They are very uncommon, and most are found incidentally during upper gastrointestinal series or esophagogastroduodenoscopy. The lesions tend to be asymptomatic, but patients may present with symptoms of duodenal obstruction or hemorrhage secondary to ulceration. Histologically, a Brunner's gland hamartoma consists of the components of Brunner's gland cells, as well as glandular, adipose and muscle cells. In this study, we report the case of a 30-year-old man who presented with upper gastrointestinal bleeding and obstructive symptoms due to a giant Brunner's gland hamartoma in the duodenal bulb. The hamartoma was successfully removed by endoscopic resection. No significant complications were observed. Microscopically, the lesion was found to be entirely composed of variable Brunner's glands and adipocytes.